The Effects of the STEM-integrated Project Based Learning (PjBL) Model on Students' Science Process Skills - Qadafi, Moammar; Doyan, Aris; Harjono, Ahmad (Journal of Science and Science Education, 2024)
Students' science process skills are still relatively low. One of the influencing factors is the choice of learning methods that are still conventional and there is no innovation in learning. This research aims to determine the effect of the STEM integrated Project Based Learning (PjBL) model on students' science process skills. This research is a quasi-experimental research with a posttest-only control group design. The data collection technique uses 20 multiple-choice questions developed by the science process skill indicators, which consist of five basic skill indicators: observing, measuring, communicating, predicting, and classification. The data analysis technique uses prerequisite tests (homogeneity and normality tests) and hypothesis testing (Manova test). Based on the results of the normality test, it was found that the data was normally distributed because it obtained a value of > 0.05. The homogeneity test results also showed that the data was distributed homogeneously because it obtained a value > 0.05. The results of hypothesis testing using the Manova test showed that science process skills were 0.000 < 0.05, so there was an influence of using the STEM-integrated PjBL model on students' science process skills. So it can be concluded that the STEM-integrated PjBL model can be said to be an innovation in learning to improve students' science process skills.